Effects of high-intensity interval training with hyperbaric oxygen - Alvarez Villela, Miguel; Dunworth, Sophia A.; Kraft, Bryan D.; Harlan, Nicole P.; Natoli, Michael J.; Suliman, Hagir B.; Moon, Richard E. (Frontiers in Physiology, 2022)
Hyperbaric Oxygen (HBO2) has been proposed as a pre-conditioning method to enhance exercise performance. Most prior studies testing this effect have been limited by inadequate methodologies. Its potential efficacy and mechanism of action remain unknown. We hypothesized that HBO2 could enhance aerobic capacity by inducing mitochondrial biogenesis via redox signaling in skeletal muscle. HBO2 was administered in combination with high-intensity interval training (HIIT), a potent redox stimulus known to induce mitochondrial biogenesis. Aerobic capacity was tested during acute hypobaric hypoxia seeking to shift the limiting site of whole body V̇O2 from convection to diffusion, more closely isolating any effect of improved oxidative capacity. Healthy volunteers were screened with sea-level (SL) V̇O2peak testing. Seventeen subjects were enrolled (10 men, 7 women, ages 26.5±1.3 years, BMI 24.6±0.6 kg.m-2, V̇O2peak SL=43.4±2.1). Each completed 6 HIIT sessions over 2 weeks randomized to breathing normobaric air, “HIIT+Air” (PiO2=0.21 ATM) or HBO2 (PiO2=1.4 ATM) during training, “HIIT+HBO2” group. Training workloads were individualized based on V̇O2peak SL test. Vastus Lateralis (VL) muscle biopsies were performed before and after HIIT in both groups. Baseline and post-training V̇O2peak tests were conducted in a hypobaric chamber at PiO2=0.12 ATM. HIIT significantly increased V̇O2peak in both groups: HIIT+HBO2 31.4±1.5 to 35.2±1.2 mL·kg-1·min-1 and HIIT+Air 29.0±3.1 to 33.2±2.5 mL·kg-1·min-1 (p=0.005) without an additional effect of HBO2 (p=0.9 for interaction of HIIT x HBO2). Subjects randomized to HIIT+HBO2 displayed higher skeletal muscle mRNA levels of PPARGC1A, a regulator of mitochondrial biogenesis, and HK2 and SLC2A4, regulators of glucose utilization and storage. All other tested markers of mitochondrial biogenesis showed no additional effect of HBO2 to HIIT. When combined with HIIT, short-term modest HBO2 (1.4 ATA) has does not increase whole-body V̇O2peak during acute hypobaric hypoxia. (ClinicalTrials.gov Identifier: NCT02356900; https://clinicaltrials.gov/ct2/show/NCT02356900)